Técnica adaptativa de elementos finitos para análise limite e de "Shakedown" para cascas finas axi-simétricas - Felicio Bruzzi Barros (1996)
Improvements in the technique for finite element shakedown and limit analysis of axisymmetrical shells, proposed by [Franco, 1987], are presented. Basic concepts of the continuum mechanics are first summarized and the technique is introduced.l The stress problem due to the temperature gradient at the contact of a supporting skirt of a coke drum is analyzed. The elastic solution obtained from the thin shell theory was implemented for considering indirect load. An error estimator combined with adaptive procedures for an h-refinement are presented to obtain much more reliable solutions.A new finite element compatible with a more sophisticated yield surface is developed. Although the formulation for a complete shakedown analysis has not been implemented, limit analysis problems were studied for each proposed topic which illustrate the effectiveness and quality of the formulations.